How Health Plan Enrollees Value Prices Relative to Supplemental Benefits and Service Quality - Christian Bünnings; Hendrik Schmitz; Harald Tauchmann; Nicolas R. Ziebarth (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
This paper empirically assesses the relative role of health plan prices, service quality and optional benefits in the decision to choose a health plan. We link representative German SOEP panel data from 2007 to 2010 to (i) health plan service quality indicators, (ii) measures of voluntary benefit provision on top of federally mandated benefits, and (iii) health plan prices for almost all German health plans. Mixed logit models incorporate a total of 1,700 health plan choices with more than 50 choice sets for each individual. The findings suggest that, compared to prices, health plan service quality and supplemental benefits play a minor role in making a health plan choice. – – Dieses Papier untersucht empirisch die Rollen von Beitrag, Servicequalität und freiwilligen Zusatzleistungen im Rahmen der Krankenkassenwahl. Dazu verknüpfen wir repräsentative Paneldaten des SOEP der Jahre 2007 bis 2010 mit kassenspezifischen Indikatoren für (i) die Servicequalität, (ii) das Angebot von freiwilligen Zusatzleistungen und (iii) den Beitrag von fast allen deutschen Krankenkassen. Die verwendeten mixed logit Modelle basieren auf 1 700 individuellen Entscheidungssituationen, welche jeweils mehr als 50 Krankenkassen zur Wahl beinhalten. Die Ergebnisse deuten an, dass Servicequalität und freiwillige Zusatzleistungen eine - im Vergleich zu Beiträgen - untergeordnete Rolle in der Wahl der Krankenkasse spielen.
Keywords: D12; H51; I11; I13; I18; 330; service quality; non-essential benefits; prices; health plan switching; German sickness funds; SOEP